The Effect of Operating Cash Flow, Operating Capacity and Sales Growth on Financial Distress - Nur Aini Sugiana; Wastam Wahyu Hidayat (Indonesian Journal of Business Analytics, 2023)
This study aims to examine the effect of operating cash flow, operating capacity, and sales growth on financial distress. The population in this study is all properties & real estate sector companies. The samples in this study were obtained as many as 10 company samples with 5 years of research so that as many 50 research data were obtained. The analysis method used is multiple linear regression using SPSS software version 26. The results showed that operating cash flow has no effect on financial distress, operating capacity has a positive effect on financial distress, and sales growth has no effect on financial distress. Operating cash flow and sales growth do not affect financial distress because the company’s operating cash flow and sales growth tend to be small, while operating capacity has a positive effect on financial distress tends to be high because the company’s operating capacity tends to be high.